2017
DOI: 10.1038/srep42835
|View full text |Cite|
|
Sign up to set email alerts
|

Ectopic expression of Arabidopsis Target of Rapamycin (AtTOR) improves water-use efficiency and yield potential in rice

Abstract: The target of Rapamycin (TOR) present in all eukaryotes is a multifunctional protein, regulating growth, development, protein translation, ribosome biogenesis, nutrient, and energy signaling. In the present study, ectopic expression of TOR gene of Arabidopsis thaliana in a widely cultivated indica rice resulted in enhanced plant growth under water-limiting conditions conferring agronomically important wateruse efficiency (WUE) trait. The AtTOR high expression lines of rice exhibited profuse tillering, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 50 publications
(89 reference statements)
2
57
0
Order By: Relevance
“…Mutations in the LETHAL WITH SEC THIRTEEN8 (LST8), a member of the TOR complex, resulted in reduced vegetative growth (Moreau et al ., ), while silencing of Arabidopsis TOR kinase led to reduced shoot and root growth (Deprost et al ., ). Vice versa, over‐expression of Arabidopsis TOR in rice led to an increase in the number of lateral roots (Bakshi et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mutations in the LETHAL WITH SEC THIRTEEN8 (LST8), a member of the TOR complex, resulted in reduced vegetative growth (Moreau et al ., ), while silencing of Arabidopsis TOR kinase led to reduced shoot and root growth (Deprost et al ., ). Vice versa, over‐expression of Arabidopsis TOR in rice led to an increase in the number of lateral roots (Bakshi et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In plants, links between key components of the TOR pathway and ABA responses have been reported. In a recent study, ectopic expression of the Arabidopsis TOR kinase in rice was shown to induce insensitivity to ABA at the seed germination stage (Bakshi et al ., ). Over‐expression of TAP46 (the plant counterpart of TAP42; Ahn et al ., ) caused hypersensitivity to ABA and decreased PP2A activity when over‐expressed in Arabidopsis.…”
Section: Discussionmentioning
confidence: 97%
“…6, Table S2). Although the ectopic overexpression of AtTOR improved rice photosynthesis and water use efficiency, especially under water limitation (Bakshi et al, 2017), most studies conducted on Arabidopsis showed that the TOR signalling pathway plays a critical role in young developing sink tissues rather than in source leaves (Anderson et al, 2005;Deprost et al, 2005Deprost et al, , 2007Leiber et al, 2010;Xiong et al, 2013;Montané and Menand, 2013). This could explain why TOR was not activated by HL and glucose accumulation in the source leaves of S. viridis.…”
Section: Ll and Hl Altered Sugar Levels And Elicited Unexpected Sugarmentioning
confidence: 99%
“…TOR promotes plant development and growth under favourable environmental conditions (Dobrenel et al, 2011;Henriques et al, 2014;Rexin et al, 2015;Xiong and Sheen, 2015). Studies using TOR-specific inhibitors, mutants and transgenic plants showed that the TOR complex is involved in the glucose-dependent induction of photosynthesis, water use efficiency, chlorophyll metabolism, photosynthetic gene expression, stress tolerance, growth and yield A c c e p t e d M a n u s c r i p t 5 (Xiong et al, 2013;Dong et al, 2015;Li et al, 2015b;Xiong et al, 2017;Bakshi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in the model plant Arabidopsis thaliana has revealed that TORC1, which consists of TOR, Raptor (regulatory-associated protein of mTOR) and LST8 (lethal with SEC13 protein 8), promotes plant growth and cell proliferation by modulating a myriad of biological processes, including transcription, translation, ribosome biogenesis, autophagy, and primary and secondary metabolism (Dobrenel et al, 2011(Dobrenel et al, , 2016Henriques et al, 2014;Xiong & Sheen, 2014Rexin et al, 2015;Xiong et al, 2016;Zhang et al, 2016). Ectopic expression of Arabidopsis TOR improves water use efficiency and yield potential in transgenic rice (Bakshi et al, 2017). However, whether TORC1-steered growth affects plant immunity and, hence, whether TOR orchestrates growth-defense trade-offs in plants remains to be tested.…”
Section: Introductionmentioning
confidence: 99%